PV generators combined with UPQC based on a dual converter structure - Fernao Pires, Vitor (2017)
In this paper a power converter topology where an Unified Power Quality Conditioner (UPQC) is combined with the photovoltaic generators is presented. This topology is based on a dual structure of the classical three-phase two level inverters. Thus, multilevel operation is achieved with the advantages of this type of inverters. Another feature of this structure is the higher reliability of the combined system. In fact, even with a fault in one of the inverters the system can still operate. Voltage and current controllers are also described. The current and voltage controllers are implemented in the synchronous rotating reference frame (dq0-axis). Several results are presented in order to verify the operation of the system under various conditions.